EFFECTS OF SQUARE STEPPING EXERCISE ON COGNITIVE FUNCTION AND MOOD AMONG OLDER ADULTS LIVING IN NURSING HOMES - Gilang Dwi Pratiwi; Vita Lucya (Jurnal Keperawatan PPNI Jawa Barat, 2025)
Background: Older adults living in nursing homes experience environmental and social conditions that differ from those of community-dwelling elderly individuals, which may negatively affect cognitive function and psychosocial well-being, including mood. Non-pharmacological interventions that simultaneously address cognitive and emotional health are therefore needed in long-term care settings. Objective: This study aimed to evaluate the effectiveness of square stepping exercise accompanied by music in improving cognitive function and mood status among elderly individuals residing in nursing homes. Methods: A quasi-experimental study using a one-group pretest–posttest design was conducted among 33 elderly participants selected through purposive sampling. Cognitive function was assessed using the Mini-Mental State Examination (MMSE), and mood status was evaluated using the Brief Mood Introspection Scale (BMIS). The intervention consisted of square stepping exercise performed for 30 minutes per session, three times per week, over a four-week period. Data were analyzed using paired statistical tests. Results: The mean baseline MMSE score was 23.8 ± 2.17, and the mean BMIS score was 38.1 ± 4.97. Significant improvements were observed in both cognitive function and mood status following the intervention (p < 0.05 for both outcomes). Conclusion: Square stepping exercise accompanied by music effectively enhances cognitive function and mood status among elderly individuals living in nursing homes. This intervention may serve as a feasible and beneficial non-pharmacological strategy to support the overall well-being of older adults in institutional care.